The Impact of Inter-ethnic Friendship on the Social Capital of Chinese Adolescents - Qu, Jing; Liu, Jingyu (Transactions on Economics, Business and Management Research, 2024)
Inter-ethnic friendship plays a crucial role in inter-ethnic contact and serves as a significant aspect of informal interaction diversity within the realm of educational ethnic diversity. Utilizing the theoretical framework of social capital, the Poisson fixed-effect model has confirmed the beneficial impact of inter-ethnic friendships on individuals' social capital. The research revealed a significant disparity in social capital stock between students who cultivate inter-ethnic friendships and those who maintain friendships within their own ethnic group, with the former group exhibiting a 30.5% higher level of social capital. Additionally, the study identified ethnic variations in the social capital returns of inter-ethnic friendships, with minority students experiencing notably higher returns compared to Han students.